STUDY ON CONSUMER PREFERENCE OF ONLINE PUBLIC TRANSPORTATION AMONG STUDENTS IN MALANG - ADITIA, DEO WAHYU (Jurnal Ilmiah Mahasiswa FEB, 2019)
This study aims to empirically examine the effect of mobility, price, promotion, and service experiences on consumption behavior taken by researchers. This analysis uses independent variables namely mobility, price, promotion, and service. The dependent variable is consumption behavior.The research sample is active students who study in Malang. The sample is done by purposive sampling method. Data collection was carried out with questionnaires distributed directly to respondents as many as 100 questionnaires. The statistical method uses Partial Least Square Analysis by testing the t-statistic testing hypothesis. This study also used Logistic Regression and Linear Regression as the help testing.The results of this study indicate that promotion significantly positively influences consumption behavior taken by respondents, mobility, price, and service significantly negatively affect the consumption behavior taken by respondents.Keywords: Online Transportation, Partial Least Square, Logistic Regression, Linear Regression, Purposive Sampling